A proposed strategy in the light of the knowledge of knowledge to develop reading comprehension skills among sixth grade pupils in Taif Governorate - Al Thubaiti, Maryam Saeed Mohammed (Journal of Educational and Psychological Sciences, 2018)
The aim of this study was to find out the effectiveness of a proposed strategy in the light of knowledge and knowledge to develop reading comprehension skills among sixth graders. To achieve this goal, the researcher used the experimental approach based on quasi-experimental design. The sample of the study consisted of (29) students from the sixth grade primary school in the 16 th elementary school in Taif governorate. The sample was divided into two groups: experimental The study reached several results revealed the effectiveness of the proposed strategy in the development of reading comprehension skills at the levels of (direct understanding, deductive understanding, critical understanding, taste comprehension, And the creative understanding) of the experimental group students; they obtained a general average grade of (20.00), compared to the control group averaging (8.85) by an average difference (11.15) (0.65) which show a significant impact, and in the light of the results of Aldr Current Study was presented a set of recommendations and proposals.